Farm-based Evaluation of Sustainable Alternative Irrigation Practices - Oad, S. J.; Maqsood, H.; Qureshi, A. L.; Ahmed, S.; Channa, I. A.; Ali, M. I. (Engineering, Technology & Applied Science Research, 2019)
Water management is one crucial component of agribusiness and municipal policy. One of the water-oriented dimensions is irrigation. In Pakistan, there is a lack of water system planning and water conservation management. This study is an effort to focus on water conservation and optimum crop yield using cost effective irrigation practices. This study is based on the comparative analysis among four irrigation techniques: flood irrigation (conventional), furrow, alternate furrow, and raised bed on wheat crop in order to decide the most efficient irrigation technique on clay loam soil. The wheat crop was cultivated in Rabi season from November 2015 to March 2018 on a one-acre area of a local farmer of Sajawal district, Sindh. Randomize complete block design (RCBD) method was used to design and allocate 3 irrigation sub-plots. The results show significance p